KEMAMPUAN DISPOSISI MATEMATIS MAHASISWA STKIP MUHAMMADIYAH ACEH BARAT DAYA - Rismawati Rismawati (Jurnal Karya Pendidikan Matematika, 2022)
The purpose of this study was to determine the ability of students' mathematical disposition at one of the college in Aceh Barat Daya district. This research is descriptive quantitative, the data collection technique used was a mathematical disposition questionnaire. The research subjects are 21 students of mathematics education program, the results of the research show that for the indicator of confidence in learning mathematics, 67.1 is less in the category, the indicator of flexibility in doing math work is 76.7 medium category, indicator is persistent and tenacious in doing math tasks 75.0 medium category, indicator has curiosity in learning mathematics 83.5 moderate category, indicator reflects on the way of thinking and performance on oneself in learning mathematics 77.8 medium category, indicator appreciating math application 74.4 medium category, and indicator appreciating the role of mathematician 85 high category. Suggestions in this study are expected in the process of learning mathematics to give enthusiasm and motivation to students to learn mathematics by using various methods that are interesting and show usefulness in learning mathematics and increase confidence in learning mathematics.